2018
DOI: 10.1080/08037051.2018.1476055
|View full text |Cite
|
Sign up to set email alerts
|

Increased arterial stiffness – similar findings in patients with inflammatory bowel disease without prior hypertension or diabetes and in patients with well-controlled hypertension

Abstract: Chronic subclinical inflammation is responsible for dyslipidemia and accelerated atherosclerosis which consequently alterates arterial elasticity. Inflammatory bowel disease and its duration should also be considered a risk factor for subclinical organ damage, as well as hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…The findings of the present study corroborate the available preexisting data that inflammatory bowel disease severity is associated with a significant vascular impairment [8][9][10][11][12]14,17,30,34,35,[62][63][64][65][66][67][68][69][70][71][72]. The enrolled IBD subjects presented an advanced systemic inflammatory status in both groups.…”
Section: Baseline Vascular Markers Analysissupporting
confidence: 90%
“…The findings of the present study corroborate the available preexisting data that inflammatory bowel disease severity is associated with a significant vascular impairment [8][9][10][11][12]14,17,30,34,35,[62][63][64][65][66][67][68][69][70][71][72]. The enrolled IBD subjects presented an advanced systemic inflammatory status in both groups.…”
Section: Baseline Vascular Markers Analysissupporting
confidence: 90%
“…Starting from 2010, it was repeatedly reported that aortic stiffness is increased in adults patients with IBD compared with matched controls. 32 50,51 To date, at least 13 single-center cross-sectional studies 33 45 and 2 multicenter longitudinal studies 37,50,51 suggest that aortic stiffness and reflected waves are increased in adult patients with CD and UC, even after adjustment for known CV risk factors (Table 1) and that the severity and duration of inflammation over time has a key role in the arterial stiffening process. These results have been confirmed in 4 aggregated data 32,46,47,48 and 1 individual participant data meta-analysis 49 performed in patients with IBD, which are in agreement with similar findings reported in patients with rheumatoid arthritis, systemic lupus erythematosus, systemic sclerosis, and periodontitis 16 18,53 and could suggest that arterial stiffness is a vascular biomarker of chronic inflammation.…”
Section: Aortic Stiffness Is Increased In Ibd and In Patients With Chmentioning
confidence: 99%
“…Recently, independent groups reported that not only premature atherosclerosis (ie, intima-media thickening) but also arteriosclerosis (aortic stiffening) is detectable in patients with IBD and associated with chronic inflammation. 32 47,49 Moreover, the reduction of inflammation can lead to the normalization of aortic stiffness. 37,50,51 These findings, revealing strength of association, temporality, consistency, biological plausibility and gradient, as well as coherence with previous studies performed in other models of chronic inflammation, make it probable that, like premature atherosclerosis, increased aortic stiffness is also an extraintestinal manifestation of IBD.…”
Section: Increased Aortic Stiffness Is An Extraintestinal Manifestatimentioning
confidence: 99%
“…[3,[5][6][7][8] Higher pulse wave velocity (PWV) and augmentation index (AIx) were found in IBD patients and increased arterial stiffness was proposed to be linked to higher CV risk in IBD patients. [9][10][11][12][13][14][15] Observed increased arterial stiffness in IBD patients without presence and cumulative effect of other CV risk factors further contributes to the "IBD paradox" and some authors suggested that increased arterial stiffness in IBD might be a link between chronic inflammation and increased CV risk in IBD patients. [5,9,14] Zanoli et al proposed that different mechanisms lead to arterial stiffness in IBD compared to chronic kidney disease (CKD) suggesting chronic inflammation, but not aging and blood pressure (BP), as the most important risk factor for increased PWV in IBD patients which is in line with observations that disease duration is strongly associated with arterial stiffness.…”
Section: Introductionmentioning
confidence: 99%